A Computation Offloading Method for Edge Computing With Vehicle-to-Everything - Xiaolong Xu; Yuan Xue; Xiang Li; Lianyong Qi; Shaohua Wan (IEEE Access, 2019)
Nowadays, for improving the increasingly crowded traffic conditions, internet of vehicles (IoV) emerges. In IoV, the increase of smart vehicle applications produces computation-intensive tasks for vehicles. However, it is tough for vehicles to meet the demands required by tasks thoroughly due to the limited computing capacity deployed in vehicles. To address this challenge, the vehicle-to-everything (V2X) communication is a promising technology to support edge computing transmitting tasks across vehicles. By employing vehicle-to-infrastructure communication (V2I) and vehicle-to-vehicle communication (V2V), the origin vehicle seeks the feasible routes of offloading the computing tasks to the edge node (EN). In this paper, a computation offloading method which employs V2X technology for data transmission in edge computing, named V2X-COM, is proposed. Technically, the routing of the computing tasks is determined first. Then, non-dominated sorting genetic algorithm III (NSGA-III) is adopted to generate balanced offloading strategies. Furthermore, simple additive weighting (SAW) and multiple criteria decision making (MCDM) are employed to seek out the optimal offloading strategy. Finally, experimental evaluations are conducted to prove the validity of V2X-COM.